2019
DOI: 10.1103/physrevb.99.125417
|View full text |Cite
|
Sign up to set email alerts
|

Control of superconducting pairing symmetries in monolayer black phosphorus

Abstract: Motivated by recent experimental progress, we study the effect of mechanical deformations on the superconducting pairing symmetries in monolayer black phosphorus (MBP). Starting with phonon-mediated intervalley spin-singlet electron-electron pairing and making use of realistic band parameters obtained through firstprinciples calculations, we show that the application of weak mechanical strain in the plane of MBP can change the effective s-wave and p-wave symmetry of the superconducting correlations into effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 65 publications
(96 reference statements)
1
24
0
Order By: Relevance
“…It is worth mentioning that similar theory study as the present paper was conducted for black phosphorus monolayer in Ref. 51. It was found that a significant transition from effective s-wave (p-wave) to d-wave ( f -wave) symmetry class is accessible simply by the exertion of strain into the plane of black phosphorus monolayer.…”
Section: Introductionsupporting
confidence: 72%
“…It is worth mentioning that similar theory study as the present paper was conducted for black phosphorus monolayer in Ref. 51. It was found that a significant transition from effective s-wave (p-wave) to d-wave ( f -wave) symmetry class is accessible simply by the exertion of strain into the plane of black phosphorus monolayer.…”
Section: Introductionsupporting
confidence: 72%
“…As recently demonstrated, control of these parameters is possible by, for example, applying strain to the system. [9][10][11] To further shed light on the symmetry profiles of these superconducting correlations, in Figs. 1-3, we present a few representative profiles for the real and imaginary parts of the equal-Pspin and opposite-Pspin components as a function of the momenta k x and k y .…”
Section: A Symmetry Profile Of Superconducting Pair Correlationsmentioning
confidence: 99%
“…Such situations can be precisely determined by first-principles calculations; e.g., when the system experiences external strain or is subject to doping and intercalation. A practical example is when a black phosphorus mono- layer is under the application of an external strain, as was recently discussed [9][10][11] . The band-structure parameters were obtained using density-functional-theory computations, and symmetry calculations demonstrated that the momenta coefficients can change sign depending on the strength and direction of the applied in-plane strain.…”
Section: A Symmetry Profile Of Superconducting Pair Correlationsmentioning
confidence: 99%
See 2 more Smart Citations